2015
DOI: 10.1007/s11661-015-3164-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Initial Grain Size on Microstructure and Mechanical Properties of Extruded Mg-9Al-0.6Zn Alloy

Abstract: The effect of initial grain size on the microstructural evolution and tensile properties of an extruded Mg-9Al-0.6Zn alloy was investigated using homogenized billets with grain sizes of 411 and 87 lm. It is found that although dynamically recrystallized (DRXed) grains remain the same size regardless of the initial grain size, a finer-grained billet results in a significant reduction of the size and area fraction of un-DRXed grains through an increase in grain boundaries capable of acting as nucleation sites fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…%) with UTS varying from 397.8 to 418.6 MPa and elongation values over 12%. Park et al [37] reported that the UTS of the Mg-9Al-0.6Zn alloy reached 375 MPa after extrusion at a billet temperature of 523 K (250 °C), extrusion speed of 1 mm/s and a reduction ratio of 7.35. Bu et al [38] developed a new magnesium alloy containing large amounts of alloying elements, including La and Gd (Mg-Al-Zn-RE).…”
Section: Introductionmentioning
confidence: 99%
“…%) with UTS varying from 397.8 to 418.6 MPa and elongation values over 12%. Park et al [37] reported that the UTS of the Mg-9Al-0.6Zn alloy reached 375 MPa after extrusion at a billet temperature of 523 K (250 °C), extrusion speed of 1 mm/s and a reduction ratio of 7.35. Bu et al [38] developed a new magnesium alloy containing large amounts of alloying elements, including La and Gd (Mg-Al-Zn-RE).…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium alloys with high alloying content will dynamically precipitate a large number of fine, second-phase particles during extrusion, which will affect the DRX behavior of the alloy through its grain boundary pinning effect [ 100 , 101 , 102 ]. In addition to dynamically formed precipitates, the original microstructure of the magnesium alloys before extrusion also affects DRX behavior during the extrusion process, for instance, smaller original grains provide more high-angle grain boundaries and more points for DRX nucleation and promote DRX behavior during extrusion [ 103 ]. The extrusion parameters also affect DRX behavior, for instance, small extrusion ratio and low extrusion temperature can lead to incomplete recrystallization behavior, which can promote strength at the expense of ductility.…”
Section: Strengthening Mechanism Of Extrusionmentioning
confidence: 99%
“…In particular, it is more effective in cast Mg alloys, where more than 90% are used as cast products, because it can suppress hot cracking during casting and ensure a fine and uniform distribution of solute elements and second-phase particles, thereby improving the mechanical strength and ductility of the as-cast component [5][6][7]. This technique is also very important in reducing product cost because feedstock materials with a fine and homogeneous structure can reduce heat treatment times and process sequences owing to their improved formability, encompassing rollability and extrudability [8,9].…”
Section: Introductionmentioning
confidence: 99%